Successful management of ventral abdominal hernia in goat: a case report - Das, BC; Nath, BK; Pallab, MS; Mannan, A; Biswas, D (International Journal of Natural Sciences, 2012)
The study was conducted a four month old Jamunapari doe weighing 15kg that was brought to the SAQ teaching veterinary Hospital, CVASU, Chittagong with the history of unknown cause, loss of appetite and gradual swelling in the pelvic region since one month. Based on clinical examination the case was subjected as a ventral abdominal hernia and corrected by surgical intervention. The case was recovered unevenfully at 10th postoperative day. DOI: http://dx.doi.org/10.3329/ijns.v2i2.11387 International Journal of Natural Sciences (2012), 2(2):60-62